1979
DOI: 10.1161/01.cir.59.6.1098
|View full text |Cite
|
Sign up to set email alerts
|

Amrinone: a new non-glycosidic, non-adrenergic cardiotonic agent effective in the treatment of intractable myocardial failure in man.

Abstract: Chronic congestive heart failure not controlled by conventional therapy was treated with intravenous amrinone, a new non-glycosidic, non-catecholamine cardiotonic agent. Eight patients with New York Heart Association functional class III-IV symptoms were hemodynamically monitored. At peak effect, cardiac index (CI) increased from 1.84 +/- 0.32 to 2.74 +/- 0.44 l/min/m2 (mean +/- SD) (p less than 0.001) and left ventricular filling pressure (LVFP) decreased from 25.8 +/- 6.2 to 19.5 +/- 6.8 mm Hg (p less than 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
1

Year Published

1979
1979
1989
1989

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(30 citation statements)
references
References 8 publications
3
26
1
Order By: Relevance
“…Preliminary results in patients (Benotti et al, 1978;Le Jemtel et al, 1979) have confirmed our findings in the dog.…”
Section: Discussionsupporting
confidence: 86%
“…Preliminary results in patients (Benotti et al, 1978;Le Jemtel et al, 1979) have confirmed our findings in the dog.…”
Section: Discussionsupporting
confidence: 86%
“…The inotropic effect of amrinone has already been widely reported (Alousi er al., 1978; Benotti er al., Endelson er al., 1981;Farah and Alousi, 1978;Lejmetel et al, 1979). In humans, these inotropic effects are characterized by an increase in the rate of left ventricular pressure development and cardiac output accompanied by a decrease in ventricular filling pressure (Benotti et al, 1978;Lejmetel et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Amrinone (Sterling-Winthrop), a new bipyridine analogue, has recently been reported to improve cardiac function in refractory congestive cardiac failure (Benotti et al, 1978;LeJemtel et al, 1979), possibly as the result of phosphodiesterase inhibition (Honerjager et al, 1981;Endoh et al, 1982). Platelet function alterations induced by amrinone have been evaluated in both in vitro studies and in an animal model (Rao et al, 1981).…”
Section: Introductionmentioning
confidence: 99%